In‐depth virological assessment of kidney transplant recipients with COVID‐19. Issue 11 (12th September 2020) - Benotmane, Ilies; Gautier‐Vargas, Gabriela; Wendling, Marie‐Josée; Perrin, Peggy; Velay, Aurélie; Bassand, Xavier; Bedo, Dimitri; Baldacini, Clément; Sagnard, Mylène; Bozman, Dogan‐Firat; Della‐Chiesa, Margaux; Solis, Morgane; et al.
Abstract : Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) has spread widely, causing coronavirus disease 2019 (COVID‐19) and significant mortality. However, data on viral loads and antibody kinetics in immunocompromised populations are lacking. We aimed to determine nasopharyngeal and plasma viral loads via reverse transcription‐polymerase chain reaction and SARS‐CoV‐2 serology via enzyme‐linked immunosorbent assay and study their association with severe forms of COVID‐19 and death in kidney transplant recipients. In this study, we examined hospitalized kidney transplant recipients with nonsevere (n = 21) and severe (n = 19) COVID‐19. SARS‐CoV‐2 nasopharyngeal and plasma viral load and serological response were evaluated based on outcomes and disease severity. Ten recipients (25%) displayed persistent viral shedding 30 days after symptom onset. The SARS‐CoV‐2 viral load of the upper respiratory tract was not associated with severe COVID‐19, whereas the plasma viral load was associated with COVID‐19 severity ( P  = .010) and mortality ( P  = .010). All patients harbored antibodies during the second week after symptom onset that persisted for 2 months. We conclude that plasma viral load is associated with COVID‐19 morbidity and mortality, whereas nasopharyngeal viral load is not. SARS‐CoV‐2 shedding is prolonged in kidney transplant recipients and the humoral response to SARS‐CoV‐2 does not show significant impairment in this series of transplant recipients. Abstract : In kidney transplant recipients diagnosed with COVID‐19, SARS‐CoV‐2 shedding from the upper respiratory tract is prolonged, plasma viral load is associated with disease severity and mortality, and antiviral humoral responses are not severely impaired.